Pengaruh Model Pembelajaran Kooperatif Tipe NHT Terhadap Hasil Belajar Peserta Didik Pada Materi Pengukuran Bangun Datar Di Kelas IV SD Negeri 62 Banda Aceh - Lili Mardiyanti; Fauzi Fauzi; Yamin M (Universitas Syiah Kuala, 2022)
The purpose of the study was to see the significant effect of the NHT type cooperative learning model on student learning outcomes on the material for measuring flat shapes in grade IV SDN 62 Banda Aceh. The approach used is a quantitative approach and the type of research is Pre Experimental Designs with One Group Pretest Posttest Design. The population in this study were all students in class IV SDN 62 Banda Aceh with a sample of 27 students in class IVA, consisting of 15 girls and 12 boys. The data collection technique used tests in the form of pretest and posttest while to analyze the data used t-test statistics. The results showed that with a significant level = 0.05 and dk = n – 1 = 27 – 1 = 26 so that the distribution list is t with t(1- )(n-1) = t(0.95)(26) then we get t(0.95)(26) = 1.71 because tcount ttable, which is 21.60 1.71. This means that Ho is rejected and Ha is accepted. So the hypothesis in this study states that there is an effect of the NHT type cooperative learning model on student learning outcomes in the material for measuring flat shapes in grade IV SD Negeri 62 Banda Aceh.